Discrepancies in measuring bladder volumes with bedside ultrasound and bladder scanning in the intensive care unit: A pilot study. (May 2018) - Prentice, Donna M; Sona, Carrie; Wessman, Brian T; Ablordeppey, Enyo A; Isakow, Warren; Arroyo, Cassandra; Schallom, Marilyn
Objective: Intensive care unit patients are at risk for catheter-associated urinary tract infection. Earlier removal of catheters may be possible with accurate measurement of bladder volume. The purpose was to compare measured bladder volumes with bedside ultrasound, bladder scanner, and urine volume. Design: Prospective correlational descriptive study. Setting: Surgical/trauma intensive care unit and medical intensive care unit. Patients: Renal dialysis patients with less than 100 ml of urine in 24 h prior to urinary catheter removal and patients with suspected catheter obstruction. Measurements and main results: A physician trained in ultrasound and an advanced practice registered nurse trained in bladder scanning measured bladder volume; each blinded to the other's measurement. Device used first (ultrasound or bladder scanner) alternated daily. The intensive care unit team determined need for intermittent catheterization or treatment for suspected obstruction. Fifty-one measurements from 13 patients were obtained with results reported in milliliters. Ultrasound measurements were a mean volume of 72.1 ± 127 (range: 1.7–666) and the bladder scanner measurements were 117 ± 131 (0–529). On six occasions in five dialysis patients, urine volume measurement was available. The mean difference in ultrasound–urine volume mean difference was 0.5 ± 37.8 (range: −68 to 38.2) and the bladder scanner–urine volume was 132 ± 167 (−72 to 397). Two patients with suspected catheter obstructions had ultrasound, bladder scanner, urine volume measurements, respectively: (1) 539, 51, >300 (began voiding before catheter replaced); (2) 666, 68, 1000 with catheter replacement. Conditions leading to greatest differences were obesity, indwelling catheter and ascites. Conclusions: These results demonstrate the inaccuracy of the bladder scanner. Ultrasound measurements appear more accurate. To remove urinary catheters in patients with minimal to low urine output, serial ultrasound measurements can be used to monitor bladder volumes and return of renal function.